Altered regional brain activity and functional connectivity patterns in major depressive disorder: A function of childhood trauma or diagnosis?. (March 2022) - Luo, Qianyi; Chen, Juran; Li, Yuhong; Wu, Zhiyao; Lin, Xinyi; Yao, Jiazheng; Yu, Huiwen; Peng, Hongjun; Wu, Huawang
Abstract: Childhood trauma (CT) is a non-specific risk factor for major depressive disorder (MDD). However, the neurobiological mechanisms of MDD with CT remain unclear. In the present study, we sought to determine the specific brain regions associated with CT and MDD etiology. Fractional amplitude of low-frequency fluctuation (fALFF) and functional connectivity (FC) analyses were performed to assess alterations of intrinsic brain activity in MDD with CT, MDD without CT, healthy controls with CT, and healthy controls without CT. Two-by-two factorial analyses were performed to examine the effects of the factors "MDD" and "CT" on fALFF and FC. Moderator analysis was used to explore whether the severity of depression moderated the relationship between CT and aberrant fALFF. We found that the etiological effects of MDD and CT exhibited negative impacts on brain dysfunction including altered fALFF in the left postcentral gyrus, left lingual gyrus, left paracentral lobule (PCL), and left cuneus. Decreased FC was observed in the following regions: (i) the left lingual gyrus seed and the left fusiform gyrus as well as the right calcarine cortex; (ii) the left PCL seed and the left supplementary motor area, left calcarine cortex, left precentral gyrus, and right cuneus; (iii) the left postcentral gyrus seed and left superior parietal lobule, right postcentral gyrus, and left precentral gyrus. Furthermore, the severity of depression acted as a moderator in the relationship between CT and aberrant fALFF in the left PCL. These data indicate that MDD patients with and without trauma exposure are clinically and neurobiologically distinct.